2018
DOI: 10.1039/c8md00090e
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, expression and biochemical characterization of recombinant hyoscyamine-6β-hydroxylase from Brugmansia sanguinea – tuning the scopolamine production

Abstract: Hyoscyamine-6β-hydroxylase (H6H, EC 1.14.11.11) is a plant enzyme that catalyses the last two steps in the biosynthesis of the anticholinergic drug scopolamine, the hydroxylation of hyoscyamine to 6β-hydroxyhyoscyamine (anisodamine) and subsequent oxidative ring-closure to the 6,7-β-epoxide. A gene homologue was isolated from the plant () and recombinantly cloned into , expressed and purified using an effective SUMO-fusion procedure. Enzymatic activity is approximately 40-fold higher for the first reaction ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In 2018, Fischer et. al., published results of SUMO-tagged H6H from Brugmansia sanguinea to have a K m value of ~60μM [ 112 ].…”
Section: Biotechnological Approaches Of Scopolamine Production Andmentioning
confidence: 99%
“…In 2018, Fischer et. al., published results of SUMO-tagged H6H from Brugmansia sanguinea to have a K m value of ~60μM [ 112 ].…”
Section: Biotechnological Approaches Of Scopolamine Production Andmentioning
confidence: 99%
“…In vitro assays showed that atropine is enzymatically converted into scopolamine via the intermediate anisodamine [27]. This chemical transformation is conceptualized as two concerted reactions: (i) the hydroxylation of atropine followed by (ii) the cyclization of anisodamine to form an epoxide between the carbon atoms C6 and C7.…”
Section: Discussionmentioning
confidence: 99%
“…H6H has been cloned from different Solanaceae [29]. When the heterologously expressed enzyme was incubated with atropine, it produced anisodamine and scopolamine but in a ratio of 40:1 [27]. This opens the possibility that another enzyme could perform in vivo the second reaction.…”
Section: Discussionmentioning
confidence: 99%
“…A. tanguticus may have developed the ability to produce and accumulate secondary metabolites to adapt to its environment. Accordingly, important enzymes such as the putrescine Nmethyltransferase and hyoscyamine 6 behydroxylase that participate in the biosynthetic pathway may be induced by local environment [17,18].…”
Section: Concentrations Of Tas From Different Geographic Originsmentioning
confidence: 99%